Climate change VR - Mok, Grace Jie Qi (Nanyang Technological University, 2022)
Climate change is a major concern in today’s world. There are existing Virtual Reality (VR) applications that highlight the impacts of climate change. However, one common aspect they are lacking in is that there is a lack of personal connection between players and climate change. Thus, to make up for the lack of personal connection, this final year project aims to make users actors in helping to reduce the extent of the impact of climate change on the game environment through minigames and tasks. The scope of the project is narrowed down to show the impact of climate change on forest fires.